KNOWLEDGE MANAGEMENT SYSTEMS AND THEIR ROLE IN IMPROVING EMPLOYEE PERFORMANCE: APPLIED RESEARCH IN THE GENERAL COMPANY FOR ELECTRIC POWER PRODUCTION/MIDDLE EUPHRATES - Basim K. M. Nasrawi; Mohammed Moh Arrak; Hameed Shukur AbdulAmeer Al-Azzawi (Scholar Express Journals, 2025)
The management of the public company supervises all production operations for electrical and renewable energy in a way that ensures efficiency un the implementation and adherence to establishment plans and timetables for the completion and maintenance of electrical stations. General direction and follow up of executive plans and programs, supervision of the workstations, setting goals and preparing plans. The company's work, developing project work and preparing designs for the operational energy of electrical stations. The main sections of the company consist: The general director, Finance department, Administrative department, Generation stations department, Quality department, Fuel department and Follow-up department, as shown in the following figure
Keywords: Administrative; Generation; department